India: Developmental challenges faced by a dual economy - Yuqing Yang (Global Policy, 2023)
With a population of over 1.4 billion surpassing China's in 2023, India has now become the world's most populous country. Despite its robust IT and service sectors propelling it to become the fifth-largest economy, India still grapples with low GDP per capita and significant poverty. The paradoxical nature of India's development necessitates a closer examination of its governance. Over 90% of the Indian population works outside the purview of formal democratic institutions and capital-intensive economic sectors. Challenges arise from the need to sustain a large poor population with limited resources while catering to the formal sector that generates more than half of its GDP. India's governance exhibits a deep mismatch between its institutional design, politics and developmental needs. This article explores the duality of informal and formal sectors underlying challenges in Indian governance by way of the Berggruen Governance Index.
Keywords: 320